SINFONI: A near infrared AO assisted integral field spectrometer for the VLT - Thatte, N; Tecza, M; Eisenhauer, F; Mengel, S; Krabbe, A; Pak, S; Genzel, R; Bonaccini, D; Emsellem, E; Rigaut, F; Delabre, B; Monnet, G (1998)
SINFONI, the SINgle Faint Object Near-infrared Investigation, is an instrument for the Very Large Telescope (VLT), designed to provide spectroscopy at the telescope diffraction limit in the near-infrared. This unique capability is achieved by combining two state-of-the-art developments, an integral field spectrometer (SPIFFI) and a curvature sensor based adaptive optics system (MACAO). SINFONI is a collaborative effort by the Max-Planck-Institut fur extraterrestrische Physik (MPE) and the European Southern Observatory (ESO).SINFONI will operate at the Cassegrain focus of Unit Telescope 1 (UT1) of the VLT, in conjunction with a Laser Guide Star (LGS) for almost complete sky coverage. It will provide integral field data cubes, with a hexagonal field of view ranging from similar to 1 " to 8 ", with corresponding pixel sizes of 0." 03 to 0." 25. The field of view contains 1024 spatial pixels, with similar to 100% filling factor in the focal plane. Spectra are obtained for each of the 1024 pixels. Spectral resolutions of R=2000 to R=4500 will be available, covering the J, H and K spectral windows. The high spectral resolution made will allow software OH suppression in the J and H bands. The detector is a 1024(2) HgCdTe HAWAII array from Rockwell. Spectroscopy of faint objects (m(K) < 21 and m(H) < 22) will be easily feasible.